Cardiomyopathy associated with iron overload: How does iron enter myocytes and what are the implications for pharmacological therapy? - Wijarnpreecha,K. (Informa Healthcare, 2015)
© 2015 Informa Healthcare USA, Inc. Iron overload cardiomyopathy is one of the most common causes of death in thalassemia patients. Although new iron chelating agents have been developed, the mortality rate from heart failure remains elevated as a result of iron overload. This could be due to the fact that our understanding of the underlying mechanism of iron uptake into cardiomyocytes is still unclear, thus impeding the discovery and refinement of more effective therapy for thalassemia therapeutic strategies in thalassemic iron overload cardiomyopathy. Growing evidence indicates that multiple routes of iron entry into cardiomyocytes exist under iron overload conditions. These include both L-type (LTCC) and T-type (TTCC) calcium channels, divalent metal transporter 1 (DMT1) and transferrin receptors (TfRs). In this review, the routes of iron uptake into cardiomyocytes under iron overload conditions are presented. Evidence from pharmacological interventions in support or against the possible route of iron entry of each portal in cardiomyocytes are also comprehensively summarized and discussed.